Impact of Endodontic Instrumentation on Surface Roughness of Various Nickel-Titanium Rotary Files - Zafar, Muhammad Sohail (European Journal of Dentistry, 2020)
Objectives The aim of the present study was to evaluate the surface roughness (SR) of various nickel-titanium (NiTi) rotary endodontic instruments (ProTaper Next [PTN], WaveOne Gold [WOG], and ProTaper Gold [PTG]) before and after root canal instrumentation.Materials and Methods For each type (PTN, WOG, and PTG), the endodontic instrumentation was performed using extracted mandibular molar teeth’s curved mesial root canals (curvature: 20–40 degrees) after determining the working length. Each NiTi file was cleaned, and sterilized following preparation of four root canals and characterized for surface properties before and after endodontic instrumentation using a contact-mode three-dimensional surface profiler. The data were analyzed statistically using Statistical Package for the Social Sciences for SR parameters including average surface roughness value (Sa), root mean square roughness (Sq), and peak to valley height (Sz).Results Preinstrumentation assessment revealed a significant difference for all the three SR variables (p < 0.05) for the cutting blade and the flute area. WOG instruments showed the highest SR values (p = 0.000). The postinstrumentation assessment revealed significant differences in SR values in the blade and the flute between the three groups (p < 0.05), with WOG and PTG exhibiting the highest values in the blade and flute sections, respectively.Conclusions The SR parameters of intact PTN, WOG, and PTG NiTi files vary and that was increased following the endodontic instrumentation.
Keywords: clinical endodontics; shape memory alloy; topography; fatigue resistance; root canal treatment; profilometry